Pathogenetically substantiated complex therapy program of anxiety disorders in internally displaced persons - Tolstaya, T. (Journal of Education, Health and Sport, 2021)
Victims of local armed conflicts have suffered psychological trauma, in connection with which they have specific clinical and psychological characteristics of experiencing crisis situations.Forced resettlement is accompanied by transformation of the entire system of socio-psychological relations, which ultimately risks the formation of a psychological state of maximum disintegration and maladaptation. Material and methods. A comprehensive examination of 150 patients with anxiety disorders was conducted to address this goal. Patients were both sexes, aged 20-55 years. The main group consisted of 84 patients (44 women and 40 men) who participated in the developed comprehensive therapeutic program, the control group - 66 patients (34 women and 32 men) who received standard regulated therapy. The following examination methods were used in the study: clinical-psychopathological, psychodiagnostic and statistical. A complex therapy program was developed and tested, based on the data obtained during this study. It was made for the treatment of anxiety disorders with differentiated use of psychopharmacotherapy and psychotherapy. Pharmacotherapy included differentiated use of anxiolytics, selective serotonin reuptake inhibitors (sertraline) and combined serotonin and norepinephrine reuptake inhibitors (venlafaxine, mirtazapine). During our research it was developed and tested a personalized system of psychotherapy for anxiety disorders. Analysis of indicator’s quality dynamics showed that improvement of perception of physical condition in the main group increased by 39.8% of examined, in the control - by 21.1%; the sense of action independence improved by 59.8% and 36.3%, respectively; job satisfaction by 69.8% in the main and in the control – 32.2%; feeling of spiritual realization – 71.1% and 22.1% – respectively.